Potency of cv12 acupuncture as obesity prevention through modulation of ï¡ and ï¢ estrogen receptors expression on the adipose tissue of ovariectomized mice - Rejeki, Purwo Sri; Wiyasihati, Sundari Indah; Atika, Atika (Folia Medica Indonesiana, 2017)
This study aims to determine the potency of CV 12 acupuncture as prevention of weight gain in ovariectomizedmice (OVX). Female mice strain BALB/c, 28 mice, 3-4 weeks, 25-35 grams were divided into four groups; namely K1 (n = 8, sham and vehiculum injection), K2 (n = 8, OVX and vehiculum injection), K3 (n = 7, OVX and injection of estrogen intraperitoneal 10 mg/kg/day) and K4 (n = 6, OVX and CV12 acupuncture with a frequency of 2 Hz in 10 mA of continuous spike current wave).Injection and acupuncture given every day for four weeks. Weight change in K1 (0.75 ± 2.8) grams, K2 (2.71 ± 2.4) grams, K3 (0.71 ± 0.95) g and K4 (0.93 ± 2.40) gram with a significant difference in the K2 and K4 (p = 0.011). a receptor expression in K1 (12.25 ± 2.96), K2 (5.43 ± 2.64), K3 (18.86 ± 1.57), K4 (17 ± 2.00) with a significant difference to the K2 K1, K3 and K4 with p<0.05. b receptor expression in K1 (11.38 ± 1.92), K2 (4 ± 1.41), K3 (16.86 ± 1.86), K4 (14.17 ± 5.24) with significantly different a receptor expression in visceral fat mass on the group K2 to K1, K3 and K4 with p<0.05. CV 12 acupuncture increases the expression of a and b estrogen receptor in visceral adipose tissue of OVX mice equivalently and able to prevent the increase of weight due to the estrogen withdrawal. This point could potentially be used as one of the management ofobesity prevention in menopause.